Gestión administrativa del sistema Call Center de atención al usuario en el Centro de Salud Urbano Vinces - Ayala Arana, Franklin Enrique (2020)
The quality of the health service is contingent on various factors that allow it to be efficient or not, this ranges from the suitability of its collaborators, infrastructure, equipment, stock of medicines, scheduling appointments, etc. All this makes organizations more efficient and committed to solving society's problems. The study carried out by the Urban Health Center Vinces allowed to visualize the problems that affect it in its entirety. A survey of users was conducted to get first-hand information.